Publisher Correction: Ticks parasitised feathered dinosaurs as revealed by Cretaceous amber assemblages - Enrique Peñalver (Nature Portfolio, 2018)
The originally published version of this Article was updated shortly after publication to add the word ‘Ticks’ to the title, following its inadvertent removal during the production process. This has now been corrected in both the PDF and HTML versions of the Article.